Temporal association between serious bleeding and immunization: vitamin K deficiency as main causative factor - Susi Susanah; Eddy Fadlyana; Meita Dhamayanti; Rodman Tarigan; Eko Fuji Ariyanto; Yunisa Pamela; Yuzar I. B. Ismoetoto; Rita Verita Sri; Monika Hasna; Kusnandi Rusmil (BMC, 2020)
Abstract Background Bleeding as an adverse event following immunization (AEFI) that is rarely reported in children, although it can be a parental concern. Bleeding episodes ranging in severity from mild to severe and defined as any external and/or internal bleeding can be caused by acquired or hereditary disorders. This study analyzes whether bleeding episodes in children that were recorded as AEFIs are causally associated with immunization and elaborates their etiology. Methods A cross-sectional study of 388 AEFI cases in children from West Java Provincial Committee in Indonesia confirmed by case findings from 2000 until 2017. Results Of the total number of cases studied, 55 (14%) involved children aged 5 days to 12 years who presented with bleeding and were referred to a provincial hospital. Analysis revealed that 32 cases were most likely caused by acquired prothrombin complex deficiency (APCD) and 30 of these APCD cases were strongly suspected to be manifestations of vitamin K deficiency bleeding (VKDB). All VKDB subjects were aged 5 days to 3 months without a history of administration of prophylactic vitamin K. When a World Health Organization classification was used, most bleeding cases in this study became coincidental events with a temporal association with immunization. A causality assessment suggested that these cases were causally unrelated. Conclusion Most cases of bleeding reported as an AEFI were found to be VKDB, which is considered a coincidental event following immunization with a temporal association, and an unrelated category based on the results of a causality assessment. Vitamin K should be administered to all newborns as a prophylactic and AEFI surveillance should be improved based on the low numbers of AEFI reported in Indonesia.